News from dendritic cells in atopic dermatitis - Schäkel, Knut; Hänsel, Anja (Current opinion in allergy and clinical immunology, 2011)
Purpose of review - Dendritic cells are essential for the generation of innate and adaptive immune responses, which makes them stay on center stage when studying the immuno pathogenesis of atopic dermatitis. This review will discuss recent findings on the role of dendritic cells subsets in atopic dermatitis and will report novel findings on how the microenvironment conditions dendritic cells to fuel atopic dermatitis. - Recent findings - Several microenvironmental factors characteristic for atopic dermatitis and with direct relevance for the disease have been defined. We now increasingly understand how thymic stromal lymphopoietin and histamine contribute to the disease by modulating the function of dendritic cells. We have learned much about the pathogenesis of atopic dermatitis by the studies on inflammatory dendritic epidermal cells. However, the current analysis on the functional and phenotypic heterogeneity of dendritic cells in eczematous skin lesions may lead to the definition of additional dendritic cell types relevant in the pathogenesis of atopic dermatitis. In this respect, it appears interesting to further discuss the parallels and differences in atopic dermatitis and psoriasis. - Summary - Understanding the heterogeneity of dendritic cells and their functional alteration by local factors in the inflamed skin will provide essential clues to the immunopathogenesis of atopic dermatitis.
Gesehen am 10.10.2022